Parabolic Problems The Herbert Amann Festschrift - Escher, Joachim; Guidotti, Patrick; Hieber, Matthias; Mucha, Piotr; Prüss, Jan W.; Shibata, Yoshihiro; Simonett, Gieri; Walker, Christoph; Zajaczkowski, Wojciech (Progress in Nonlinear Differential Equations and Their Applications, 2011)
The volume originates from the 'Conference on Nonlinear Parabolic Problems' held in celebration of Herbert Amann's 70th birthday at the Banach Center in Bedlewo, Poland. It features a collection of peer-reviewed research papers by recognized experts highlighting recent advances in fields of Herbert Amann's interest such as nonlinear evolution equations, fluid dynamics, quasi-linear parabolic equations and systems, functional analysis, and more.